Pengembangan Handout Materi Inovasi Teknologi Biologi Kelas X SMA Berbasis Potensi Lokal: Dadih Dalam Pembuatan Es Krim Dadih Durian - putri, widya; Syafii, Wan; mahadi, imam (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2025)
This study aims to develop a local wisdom-based handout on biology technology innovation material for class X SMA by utilizing dadih as an additional ingredient in making durian dadih ice cream. Dadih is one example of local wisdom of traditional food from West Sumatra, but local potential such as dadih has not been optimally integrated in school learning as a learning resource. In fact, dadih is very relevant to biology material, especially in learning biological technology innovations related to fermentation processes and microbiology. This research consisted of two stages, namely experiments in making durian dadih ice cream with different lengths of dadih fermentation and handout development using the ADDIE development model until the development stage. The experimental method used a completely randomized design (CRD) of 4 treatments with 3 repetitions. Parameters observed included organoleptic tests of aroma, taste, color, texture. The results showed that the best treatment was A2 treatment with dadih fermentation time for 48 hours with the category of aroma not rancid, slightly sour taste, slightly yellowish color, slightly soft texture. Furthermore, the research results were integrated into the handout design, which was validated by experts and obtained an average score of 3.7, with a very valid category. This study shows that durian dadih ice cream food products have a p-value of 3.7, with a very valid category. This research shows that durian dadih ice cream food products have great potential as innovative contextual teaching materials in learning biological technology innovation in class X high school biology learning.